Personality and compliance with COVID-19 protective measures among older Americans: Moderating effects of age, gender, and race/ethnicity. (April 2022) - Choi, Shinae L.; Martin, Peter; Cho, Jinmyoung; Ryou, Yeon Ji; Heinz, Melinda
Abstract: Following the growing evidence that personality is related to various health behaviors, we examined whether personality traits were related to compliance with COVID-19 protective measures and evaluated the extent to which associations were moderated by age, gender, or race/ethnicity among older adults during a summer 2020 surge of COVID-19 cases in the United States. Data were from the 2020 Health and Retirement Study COVID-19 module. Multivariate ordinary least squares regression analyses were computed adjusting for health, psychosocial, and sociodemographic factors. Results indicated the significant associations between personality traits and compliance with COVID-19 measures varied by age, gender, and race/ethnicity. Specifically, the associations of agreeableness with wearing a mask and frequent handwashing were less pronounced among older compared with younger individuals. The association between extraversion and wearing masks was stronger for men than for women. The associations of agreeableness with handwashing and physical distancing were weaker for Hispanic older adults, whereas the associations of extraversion with physical distancing and using sanitizers were stronger for Hispanic older adults than for their non-Hispanic White counterparts. Implications regarding behavioral science underlying the current pandemic and future public health crises are discussed. Highlights: We examine personality and compliance with COVID-19 measures in older Americans. We evaluate the extent to which associations are moderated by age, gender, or race. Higher extraversion is related to less compliance with COVID-19 protective measures. Agreeableness, conscientiousness, and openness are related to greater compliance. The inverse association between extraversion and mask wearing is stronger for men.